Elevated Growol Flour Reduce Fasting Blood Glucose, HOMA-IR and Increase Insulin Level in Rat Model with Type 2 Diabetes Mellitus - Nofia, Yasinta; Wasita, Brian; Susilawati, Tri Nugraha (Universitas Airlangga, 2022)
The rise of glucose levels in the blood of patients with type-2 diabetes mellitus (T2DM) is attributed to the decrease of insulin secretion and the interruption of insulin activity. Growol is a fermented product made from cassava that has the potential to lower blood glucose levels in patients with T2DM. This study was aimed to evaluate the effects of oral administration of growol flour on the levels of blood glucose, insulin, and HOMA-IR. A total of 40 male Wistar rats were divided into 5 groups i.e., negative control group, positive control group taking metformin, and 3 treatment groups taking growol flour of 3.1, 6.2, and 9.3 (g/200gBW), respectively, for 2 weeks. Blood glucose levels were measured using Enzymatic Photometric Method GOD-PAP, insulin using the ELISA kit, and HOMA-IR using the formula. The Shapiro Wilk test was used to determine the normality of the data followed by the One-Way ANOVA test and Posthoc Tukey HSD test. The Paired T-test was used to see the difference of pre- and post-treatment levels of blood glucose, insulin, and HOMA-IR. There was a decrease (p<0.05) in blood glucose levels and HOMA-IR after the administration of low, moderate, and high doses of growol flour. In contrast, the levels of insulin increased (p<0.05) after the administration of low, moderate, and high doses. In conclusion, growol flour contributes to the maintenance of T2DM by lowering the levels of fasting blood glucose levels, as well as HOMA-IR, and increasing the levels of insulin in rats.